Softwares contables y su relación con la mejora de los procesos contables en áreas contables de empresas comerciales de la ciudad de Iquitos año 2025 - Flores Gonzales, Farid Alexander (2025)
In an increasingly demanding business context, the digitalization of accounting management represents a key opportunity to optimize time, reduce errors and improve the quality of financial information, the study's general objective was to identify how accounting software relates to the improvement of accounting processes in accounting areas in commercial companies in the city of Iquitos during the year 2025, the methodology applied was a quantitative approach, basic-applied type, with a non-experimental correlational design, the population was made up of 94 workers from the accounting area of various commercial companies in Iquitos, using a structured questionnaire with a Likert scale with 24 items, the main results indicated that there is a significant and positive relationship between the use of accounting software and the improvement of accounting processes, with a Spearman coefficient of 0.628, likewise, a positive relationship was found between the characteristics of the software and the accounting processes, as well as between the experience in its use and its efficiency with the improvement of said processes, in the same way the descriptive results They revealed a highly favorable perception of the usefulness of accounting software, highlighting its ability to generate accurate reports, automate tasks, reduce errors, and ensure compliance with current accounting standards.